Contribution of recruitable follicles to circulating anti-Müllerian hormone levels following maximal gonadotrophin stimulation in patients with limited ovarian reserve. (3rd March 2020) - Grynnerup, Anna García-Alix; Løssl, Kristine; Pilsgaard, Fie; Bogstad, Jeanette Wulff; Prætorius, Lisbeth; Zedeler, Anne; Lunding, Stine Aagaard; Bungum, Leif; Andersen, Anders Nyboe; Pinborg, Anja
Abstract: In women, the majority of anti-Müllerian hormone (AMH) measured in serum originate from small antral follicles measuring 2–10 mm. In gonadotrophin-stimulated cycles prior to assisted reproductive technology (ART), most of the recruitable follicles develop beyond 10 mm in size and thus lose their AMH secretion capacity causing declining serum AMH levels. The aim of this study was to define the residual serum AMH level after elimination of the AMH producing recruitable follicles following maximal gonadotrophin stimulation. We measured serum AMH and number of follicles according to size at several time points during a cycle of maximal gonadotrophin stimulation (fixed dose of 300 IE HP-hMG) in 107 women with low AMH (median AMH 5 pmol/L, interquartile range (IQR) 3.3–8.3). We found that AMH decreased gradually and reached a minimum level of −55.4% (95% CI −59.6; −50.7) of the baseline value four days after ovulation trigger. Our findings suggest that the residual AMH production origins from pre-antral and small antral follicles not visible by sonography and that they account for up to 40% of the circulating AMH.